If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9z-6+49=20z-34
We move all terms to the left:
9z-6+49-(20z-34)=0
We add all the numbers together, and all the variables
9z-(20z-34)+43=0
We get rid of parentheses
9z-20z+34+43=0
We add all the numbers together, and all the variables
-11z+77=0
We move all terms containing z to the left, all other terms to the right
-11z=-77
z=-77/-11
z=+7
| −21=91k | | 6.9=x+5.9x+5.9 | | Xx5+4=6 | | 39h=12 | | 3(3x+2)=3x+x+6 | | d+19=79 | | 45=3t | | 67+6a-1=180 | | 20/3y=-13 | | x-0.40x=54 | | ∣b+18∣=50 | | 2.5x+18=-x-3 | | 4m+6+5m+3=90 | | 7x+(-2x)+8x+1x=5 | | (X2+6x-7)(2x2-8x+1)=0 | | 6n+5+4n-5=90 | | 4/x+7=10 | | 7(x=8)=-35 | | (X^2+6x-7)(2x^2-8x+1)=0 | | −21x−(21x+4)+12=17x−6(3x+65) | | 1(6x-2)=22 | | 7(x=8)=35 | | 38=x+13 | | 4x-1=2x+5x-8 | | 2(4x+10)=18 | | j/−2+7=−12+7=−12 | | 10(-x+3)=-20 | | e^2+10e-30=0 | | 2x+5+2x+7=360 | | 27=-11x+14x | | -3(4x+3)=3 | | 24(-4x+2)=0 |